Language, discourse and power in African Amarican culture - Morgan, Marcyliena (Cambridge University Press, 2002)
African American language is central to the teaching of linguistics and language in the United States, and this book covers the entire field--grammar, speech, and verbal genres, and it also the various historical strands that must be identified in order to understand the development of African American English. These are the social and cultural history of the American South, the urban and northern black popular culture, and the policy issues. It also covers the heated political and educational debates current today about the status fo the African American dialect.